Additive manufacturing of metals - Fisher, David J. (Materials research foundations, 2020)
The book reviews the various techniques that are currently in use and describes the many possible applications. Keywords: Additive Manufacturing, 3-Dimensional Printing, Layered Manufacturing, Titanium Alloys, Nickel Alloys, Iron Alloys, Stainless Steels, Aluminium, Cobalt, Copper, Magnesium, Niobium, Tantal, Tin, Tungsten, Zinc, Porous Metals, Biomedical Materials, Orthopaedic Devices, Dental Implants, Aerospace Components, Laser Melting, Electron-Beam Melting.